Hybrid zinc oxide conjugated polymer bulk heterojunction solar cells - Beek, Waldo J. E.; Wienk, Martinus Maria; Kemerink, Martijn; Yang, Xiaoniu; Janssen, René A. J. (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2005)
Bulk heterojunction photovoltaic devices based on blends of a conjugated polymer poly[2-methoxy-5-(3‘,7‘-dimethyloctyloxy)-1,4-phenylenevinylene] (MDMO−PPV) as electron donor and crystalline ZnO nanoparticles (nc-ZnO) as electron acceptor have been studied. Composite nc-ZnO:MDMO−PPV films were cast from a common solvent mixture. Time-resolved pump−probe spectroscopy revealed that a photoinduced electron transfer from MDMO−PPV to nc-ZnO occurs in these blends on a sub-picosecond time scale and produces a long-lived (milliseconds) charge-separated state. The photovoltaic effect in devices, made by sandwiching the active nc-ZnO:MDMO−PPV layer between charge-selective electrodes, has been studied as a function of the ZnO concentration and the thickness of the layer. We also investigated changing the degree and type of mixing of the two components through the use of a surfactant for ZnO and by altering the size and shape of the nc-ZnO particles. Optimized devices have an estimated AM1.5 performance of 1.6% with incident photon to current conversion efficiencies up to 50%. Photoluminescence spectroscopy, atomic force microscopy, and transmission electron microscopy have been used to gain insight in the morphology of these blends.
Gesehen am 16.12.2019